Advances in management accounting - Malina, Mary A. (Advances in management accounting, 2017)
Prelims -- Linking the ethics and management control literatures -- Managerial accounting research in corporate social responsibility: a framework and opportunities for research -- Sustainability/CSR Research in management accounting: a review of the literature -- Simons' Levers of control framework: commensuration within and of the framework -- Resolving the sunk cost conflict -- Aligning financial and management accounting policies: what drives integration? - Empirical evidence from German IFRS 8 segment reports -- Individual performance measures: effects of experience on preference for financial or non-financial measures -- Index